PROMOTIONAL STRATEGY FOR INCREASING CORN STICK SALES AT UMKM CBC (CAHAYA BINTANG CAKRAWALA) IN MOODU DISTRICT. EAST CITY GORONTALO KOTA GORONTALO - Nur Novianti Noho; sudarsono; Fitriyani Husain (Jurnal Ilmu Manajemen dan Bisnis, 2024)
The current study aims 1) The objectives of this research are 1) To find out thesales strategy for corn sticks at Cahaya Bintang Cakrawala UMKM (CBC) in Moodu. DistrictEast City Gorontalo City. 2) To find out about promotions to increase sales of jaguan sticksat UMKM CBC (Cahaya Bintang Cakawala) in Moodu, Kec. East City, Gorontalo City.The method used in this study is descriptive qualitative methods with observation data collection techniques, in-depth interviews, and documentation. The result of the study shows that 1) The promotional strategy implemented by UMKM Cahaya Bintang Cakrawala in Moodu, Kota Timur District, Gorontalo City is expanding market share by introducing goods or productson social media and frequently participating in UMKM exhibitions held by the government, Indonesian banks, private parties and in real terms through MSME product exhibitions at certain events related to the business world. Then provide promos. 2) Promotion to increase sales of cornsticksat UMKM CBC (Cahaya Bintang Cakrawala) in Moodu District. East City, Gorontalo City, by carrying out promotions to convey sales to the public by creating interesting promotional contenton social media so that consumers know about the existence of the corn stick sanduse Facebook media as a media place or means of disseminating in formation about the cornstick business and word to mouth media ormouth to mouth.